Secondary traumatic stress and vicarious posttraumatic growth in oncology nurses: the mediating role of empathy - Cai, Yitong; Liu, Ming; Li, Yifei; Li, Juan; Geng, Jie; Liu, Xiaoying; Zhang, Jingping (Frontiers in Public Health, 2024)
Background The relationship between secondary traumatic stress (STS), empathy, and vicarious post-traumatic growth (VPTG) in oncology nurses is unclear. Understanding these links is crucial for improving nurse well-being and patient care quality. Objective This study aimed to investigate the relationships between STS, empathy, and VPTG among oncology nurses. Methods This cross-sectional study was conducted in a multicentric setting. Data collection involved oncology nurses completing questionnaires assessing STS, empathy, and VPTG levels. Data analysis included correlation analyses, multiple stepwise regression analysis, and structural equation modeling (SEM) to examine the interrelationships between these variables. The study adhered to the STROBE checklist. Results A total of 391 oncology nurses participated in the study. They showed moderate to low levels of VPTG and high levels of STS. STS exhibited a negative association with VPTG, while empathy demonstrated a positive direct association with both VPTG and STS. Moreover, SEM indicated that empathy mediated the relationship between STS and VPTG, with a partial mediating effect of 0.127. Factors such as receiving psychological training, educational attainment, STS, and empathy collectively explained 24% of the variance in VPTG. Conclusion Our findings highlighted the negative correlation between STS and VPTG among oncology nurses. Additionally, empathy was found to mediate the relationship between STS and VPTG, suggesting it plays a significant role in influencing VPTG. Implications for practice To aid oncology nurses, interventions should focus on reducing STS and enhancing empathy. Strategies like resilience workshops, peer support, and stress management can foster VPTG. Creating a supportive work environment is crucial for nurses’ well-being and quality patient care.